Crosslinked solidified gel electrolytes via in-situ polymerization featuring high ionic conductivity and stable lithium deposition for long-term durability lithium battery. (20th November 2020) - Tsao, Chih-Hao; Lin, Yun-Tse; Hsu, Shun-Yuan; Okada, Shizuka; Kuo, Denial; Hou, Sheng-Shu; Kuo, Ping-Lin
Highlights: The solidified gel electrolytes (SGEs) with remarkably high ionic conductivity of 9 mS cm −1 at room temperature. The SGEs exhibit nearly 100% capacity retention after 150 cycles at 4C/4C charge/discharge. The SGEs form a uniform passivation layer on the lithium metal surface that provide good cycling durability. Abstract: A high-power lithium battery exhibits nearly 100% capacity retention after 150 cycles at 4C/4C charge/discharge is achieved by solidified gel electrolytes (SGEs) with remarkably high ionic conductivity of 9 mS cm −1 at room temperature. A series of SGEs is comprised by poly(ethylene oxide) (PEO) polymer precursor with conventional liquid electrolyte with superior lithium dendrite growth suppression that enables long-cycle life and high-power lithium batteries. The battery also improves safety with minimal gas generation at 100 °C . Solid-like property increases as the crosslinked density enhances the gelation property of the SGEs. The less crosslinked SGE preserves the great battery capacity similar to the liquid electrolyte of 64 mAh g   −   1 at 10 C rate. Furthermore, highly crosslinked SGE exhibits nearly 100% capacity retention after 150 cycles with charge/discharge rate of 4C/4C that surpassed the liquid electrolyte. SEM image shows that the SGE form a uniform passivation layer on the lithium metal surface that provide good cycling durability. By simply controlling the crosslinked density with the length of crosslinker, desired battery performance can be achieved. Consequently, these findings accelerate the practical application for the solidified gel electrolytes with superior safety and durability in lithium battery.